Pengaruh kualitas layanan dan penanganan keluhan terhadap kepuasan dan loyalitas nasabah di bank syariah mandiri kota samarinda - Rachmat Kurniawan; Herning Indriastuti; Sri Wahyuni (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
The purpose of this research is to know the influence of service quality and handling complaint on customer satisfaction and loyalty at Bank Mandiri Syariah Branch of Samarinda City. Basic theory used Service Quality, Handling Complaint, Customer Satisfaction and Customer Loyalty. Samples taken as many as 133 people with purposive sampling method. Data collected by questionnaires by using a 5-point Likert scale to measure 14 indicators. The analysis technique used is path analysis. The result of conclusions this study: Service Quality has influence and significant to Customer Satisfaction of Mandiri Syariah Bank in Samarinda City, this the research hypothesis is accepted. Handling Complaint has influence and significant to Customer Satisfaction of Mandiri Syariah Bank in Samarinda City, this the research hypothesis is accepted. Service Quality has influence and do not significant to Customer Loyalty of Mandiri Syariah Bank in Samarinda City, this the research hypothesis is accepted. Handling Complaint has influence and do not significant to Customer Loyalty of Mandiri Syariah Bank in Samarinda City, this the research hypothesis is accepted. Customer Satisfaction has influence and significant to Customer Loyalty of Mandiri Syariah Bank in Samarinda City, this the research hypothesis is accepted.